The exchange rates – indicators for assessing the financial performance of the companies from Romania - Baltes Nicolae; Dragoe Alexandra-Gabriela-Maria (Studia Universitatis Vasile Goldis Arad, Seria Stiinte Economice, 2016)
The research aims to determine the financial performance of the companies listed and traded on the Bucharest Stock Exchange from the manufacturing sector in Romania, compared with the performance recorded by the Bucharest Stock Exchange, based on the exchange rates. It was concluded that the financial performance of the companies included in the research, quantified on the basis of the exchange rates, decreased significantly with the arrival of the financial and economic crisis, currently, the companies being unable to reach the level of performance recorded before the crisis.